Conserved Roles of CrRLK1L Receptor-Like Kinases in Cell Expansion and Reproduction from Algae to Angiosperms - Galindo-Trigo, Sergio; Gray, Julie E.; Smith, Lisa M. (Frontiers in Plant Science, 2016)
Receptor-like kinases (RLKs) are regulators of plant development through allowing cells to sense their extracellular environment. They facilitate detection of local endogenous signals, in addition to external biotic and abiotic stimuli. The Catharanthus roseus RLK1-like (CrRLK1L) protein kinase subfamily, which contains FERONIA, plays a central role in regulating fertilization and in cell expansion mechanisms such as cell elongation and tip growth, as well as having indirect links to plant-pathogen interactions. Several components of CrRLK1L signaling pathways have been identified, including an extracellular ligand, coreceptors and downstream signaling elements. The presence and abundance of the CrRLK1L proteins in the plant kingdom suggest an origin within the Streptophyta lineage, with a notable increase in prevalence in the seeded land plants. Given the function of the sole CrRLK1L protein in a charophycean alga, the possibility of a conserved role in detection and/or regulation of cell wall integrity throughout the Strephtophytes is discussed. Orthologs of signaling pathway components are also present in extant representatives of non-vascular land plants and early vascular land plants including the liverwort Marchantia polymorpha, the moss Physcomitrella patens and the lycophyte Selaginella moellendorffii. Deciphering the roles in development of the CrRLK1L protein kinases in early diverging land plants will provide insights into their ancestral function, furthering our understanding of this diversified subfamily of receptors in higher plants.